2022
DOI: 10.1038/s41598-022-07341-x
|View full text |Cite
|
Sign up to set email alerts
|

Gramicidin S and melittin: potential anti-viral therapeutic peptides to treat SARS-CoV-2 infection

Abstract: The COVID19 pandemic has led to multipronged approaches for treatment of the disease. Since de novo discovery of drugs is time consuming, repurposing of molecules is now considered as one of the alternative strategies to treat COVID19. Antibacterial peptides are being recognized as attractive candidates for repurposing to treat viral infections. In this study, we describe the anti-SARS-CoV-2 activity of the well-studied antibacterial peptides gramicidin S and melittin obtained from Bacillus brevis and bee veno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Endogenous AMPs also showed antiviral activity against diverse viruses, including the human influenza virus, human immunodeficiency virus, rabies virus, West Nile virus (WNV), and herpes simplex virus (HSV) [ 25 , 67 , 68 , 69 , 70 ]. Among them, gramicidin S and melittin from Bacillus brevis and bee venom, respectively, showed noteworthy anti-SARS-CoV-2 effects with viral particle reduction compared to remdesivir, a repurposed drug used to treat the infection [ 71 ]. Antiviral activities against HSV and WNV were also reported for other cathelicidins, such as LL-37, Pb-CATH4, Hg-CATH, and ModoCath5 [ 25 , 70 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous AMPs also showed antiviral activity against diverse viruses, including the human influenza virus, human immunodeficiency virus, rabies virus, West Nile virus (WNV), and herpes simplex virus (HSV) [ 25 , 67 , 68 , 69 , 70 ]. Among them, gramicidin S and melittin from Bacillus brevis and bee venom, respectively, showed noteworthy anti-SARS-CoV-2 effects with viral particle reduction compared to remdesivir, a repurposed drug used to treat the infection [ 71 ]. Antiviral activities against HSV and WNV were also reported for other cathelicidins, such as LL-37, Pb-CATH4, Hg-CATH, and ModoCath5 [ 25 , 70 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…After brief centrifugation, the supernatant was collected and quantified using the amido black method [36]. A total of 200ug of protein was in-gel trypsin digested and labelled with iTRAQ label as per previously mentioned protocol [36][37][38][39][40]. SARS-COV-2 negative samples were labelled with iTRAQ 114 and 115, and positive samples were labelled with 116 and 117.…”
Section: Protein Extraction and Itraq Labellingmentioning
confidence: 99%
“…Authors hypothesized that the whole venom may attenuate the cytokine storm caused by SARS-CoV-2 and could be used in a prophylactic context for COVID-19 [ 71 , 72 ]; in addition, melittin was tested for in vitro assay using Vero cells and it was found that it could neutralize SARS-CoV-2 virus, showing more pronounced antiviral activity at 12 h with 95% of viral reduction; also, the effect of melittin on the ability of the virus to infect Vero cells was studied through high-throughput proteomic analysis. The omics analysis revealed that proteins were found to be down-regulated in the cells following melittin treatment, indicating that the toxin induces a metabolic effect and not merely viral lysis [ 73 ]. Although this study shows benefits of melittin against SARS-CoV-2, a formulation containing melittin must be very well adjusted so that it causes no cytolytic effects [ 73 , 74 ].…”
Section: Crosstalk Of Animal-derived Toxins and Covid-19mentioning
confidence: 99%
“…The omics analysis revealed that proteins were found to be down-regulated in the cells following melittin treatment, indicating that the toxin induces a metabolic effect and not merely viral lysis [ 73 ]. Although this study shows benefits of melittin against SARS-CoV-2, a formulation containing melittin must be very well adjusted so that it causes no cytolytic effects [ 73 , 74 ].…”
Section: Crosstalk Of Animal-derived Toxins and Covid-19mentioning
confidence: 99%